465 Analysis of Female Authorship Trends in Neurosurgery Over a 10-year period: 2010–2020. (1st April 2022) - Shah, Darsh; Kohli, Vikraant; Shah, Aayush; Surapaneni, Akhil; Tyler-Kabara, Elizabeth C.; Kuo, John S.
Abstract : INTRODUCTION: While women had greater representation in medicine in recent years, neurosurgery continues to rank towards the bottom when it comes to the proportion of women occupying a residency position in the US. Many have inferred a gender gap in the authorship of neurosurgical literature. To our knowledge, no study has analyzed changes in the representation of women among first and principal (last) authors in neurosurgery over a consecutive period. METHODS: Using the PUBMED search engine, all articles published from January 1st, 2010, to December 31st, 2020 in 10 prominent general and subspecialty neurosurgery journals were examined. Author gender was inferred using a verified online gender determination tool. RESULTS: Among the 49, 023 neurosurgery articles analyzed from 2010 to 2020, 8, 845 were published by a female first author, while 40, 178 were published by a male first author (18.0% vs. 82.0%). Moreover, among articles with at least two authors, 5, 542 were published by a female principal author, while 39, 682 were published by a male principal author (12.3% vs. 87.7%). The top three publishers in terms of the proportion of female authorship (first or last author) were all subspecialty journals. Over this 10-year period, the proportion of female first authorship increased at a greater rate than female principal authorship. The rate of increase in female first authorship was greater among general neurosurgery literature compared to subspeciality neurosurgery literature. Using binomial logistic regression, articles with a female principal author were 1.72 times more likely to have a female first author than those with a male last author. CONCLUSION: In the past decade, woman representation in original neurosurgery literature has varied by time, subspecialty, and principal authorship gender. A gradual rise in woman authorship highlights incremental progress in gender diversity and the need for expanded efforts to achieve equity in neurosurgery research.